Nieznane źródło do dziejów mennicy bydgoskiej w I połowie XVIII w. (Kronika Bydgoska, 2010)
The Bydgoszcz borough books, presently kept in the State Archive in Poznań, feature an interesting source conceming the history of the Bydgoszcz mint in the first half of the 18th century. This is a list of iron objects located in the rooms of this plant in ca. 1729. Thanks to the data contained in this text, one can also specify with a certain probability the State of the mint facilities and indicate the circumstances, under which the mint was devastated. This source completes information on the history of the Bydgoszcz mint in the first half of the 18th century; only several sources conceming this institution dating back to this period have been preserved.